2014
DOI: 10.1371/journal.pone.0100270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Humoral Immune Response to Human Leukocyte Antigens in Brazilian Renal Transplant Candidates

Abstract: Pre-transplant sensitization to human leukocyte antigens (HLA) is a risk factor for graft failure. Studies of the immunological profile related to anti-HLA antibodies in Brazilian renal transplant candidates are few. In this study, we evaluated the humoral immune response to HLA antigens in 269 renal transplant candidates, in Paraná State, Brazil. The HLA typing was performed by the polymerase chain reaction sequence-specific oligonucleotide method (PCR-SSO) combined with Luminex technology, using an SSO-LABTy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
2
3
1
Order By: Relevance
“…As with other studies, the proportion of female patients was higher in the HLAi group than in the control group [79]. This difference might be due to sensitization from pregnancy [25, 26]. The lower BMI observed in the HLAi KTRs is probably also related to the higher proportion of women.…”
Section: Discussionsupporting
confidence: 67%
“…As with other studies, the proportion of female patients was higher in the HLAi group than in the control group [79]. This difference might be due to sensitization from pregnancy [25, 26]. The lower BMI observed in the HLAi KTRs is probably also related to the higher proportion of women.…”
Section: Discussionsupporting
confidence: 67%
“…The present study compares the characteristics of different kinds of living donor, incompatible kidney transplants. Published studies report that the proportion of female patients is higher in the HLAi group due to sensitization from pregnancy 14,15,22‐26 . This was different from the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have reported high rates of leukocyte alloimmunization in renal transplant candidates. 18,19 Similarly to that reported by Hyun et al, 6 we found that the percentage of sensitized ESRD patients was 40.6%. As expected, sensitizing events were associated with higher prevalence of anti-HLA antibodies compared with patients without sensitizing events.…”
Section: Discussionsupporting
confidence: 83%